Development of twenty-one polymorphic microsatellite markers for the fungus-growing ant, Mycocepurus goeldii (Formicidae: Attini), using Illumina paired-end genomic sequencing - Rabeling, Christian; Love, Cara N.; Lance, Stacey L.; Jones, Kenneth L.; Pierce, Naomi E.; Bacci, Maurício [UNESP] (Springer, 2014)
Obligate social parasites, or inquilines, exploit the colonies of free-living social species and evolved at least 80 times in ants alone. Most species of the highly specialized inquiline social parasites are rare, only known from one or very few, geographically isolated populations, and the sexual offspring of most inquiline species mates inside the maternal colony. Therefore, inquiline populations are believed to be small and genetically homogeneous due to inbreeding. To comparatively study the genetic diversity of the socially parasitic fungus-growing ant, Mycocepurus castrator, and its only known host species, Mycocepurus goeldii, and to infer the parasite's conservation status, we developed 21 microsatellite markers for the host species, M. goeldii, and evaluated whether these markers cross-amplify in the social parasite, M. castrator. We isolated and characterized a total of 21 microsatellite loci for M. goeldii. The loci were screened for 24 individuals from geographically distant and genetically divergent populations in Brazil. The number of alleles per locus ranged from 18 to 4, the observed heterozygosity ranged from 0.25 to 0.636, and the probability of identity values ranged from 0.011 to 0.146. Preliminary analyses show that these markers cross amplify in the closely related social parasite species M. castrator. These newly developed loci provide tools for studying the genetic diversity and the evolution of social parasitism in the Mycocepurus host-parasite system.
Keywords: Polygyny; Polyandry; Social parasitism; Inquilinism; PAL_FINDER; SSR